1992
DOI: 10.1063/1.860429
|View full text |Cite
|
Sign up to set email alerts
|

Completely bootstrapped tokamak

Abstract: Numerical simulations of the evolution of large-scale magnetic fields have been developed using a mean-field Ohm's law. The Ohm's law is coupled to a A' stability analysis and a magnetic island growth equation in order to simulate the behavior of tokamak plasmas that are subject to tearing modes. In one set of calculations, the magnetohydrodynamic (MHD) -stable regime of the tokamak is examined via the construction of an Ii-q0 diagram. The results confirm previous calculations that show that tearing modes intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…(14) represents a steady-state balance between charged particles momentum gain and momentum loss expressed through the parallel current density profile [10]. Solutions of this equation can explain whether or not the turbulent contributions of Ohm's law can provide the necessary current diffusion towards the axis in operations with large bootstrap component [3,4,33]. Our work shows that all three terms play significant role in shaping the current and safety factor profile in presence of magnetic turbulence, and hence must be retained in the analysis.…”
Section: Ohm's Law and Power Balancementioning
confidence: 99%
See 1 more Smart Citation
“…(14) represents a steady-state balance between charged particles momentum gain and momentum loss expressed through the parallel current density profile [10]. Solutions of this equation can explain whether or not the turbulent contributions of Ohm's law can provide the necessary current diffusion towards the axis in operations with large bootstrap component [3,4,33]. Our work shows that all three terms play significant role in shaping the current and safety factor profile in presence of magnetic turbulence, and hence must be retained in the analysis.…”
Section: Ohm's Law and Power Balancementioning
confidence: 99%
“…Since a tokamak with large bootstrap current is ordinarily unstable to tearing modes, it has been suggested that poloidal flux generated spontaneously near the edge by the dynamo effect induced by the turbulent perturbations, can overcome this intrinsic limitation by diffusing the bootstrap current toward the center. This idea has been the driving force behind many theoretical works [3,4], as well as experimental campaigns aimed at achieving, via optimization of the plasma profiles, a steady-state "fully bootstrapped tokamak" operation [5,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The topics addressed in this paper are not unrelated to the current profile relaxation considered by Weening and Boozer, 7 but the current drive mechanisms and the mathematical approaches are different. In both cases, resistive MHD instabilities lead to the relaxation.…”
Section: Introductionmentioning
confidence: 99%
“…Most likely, given enough free energy for overlap, the system can always hover between sawtoothing and the continuum just so as to produce the time-averaged transport required under the circumstances. This is the assumption we have made in our transport model, Boozer formulated a similar model for magnetic helicity transport, using hyper-resistive transport due to momentum diffusion [9].…”
mentioning
confidence: 99%
“…where the left side is the approximate free energy bound for both magnetic energy and pressure-driven modes, and on the right we have expressed the perturbation 6B in terms of the island width w by the usual formula [9], L s = q/q' being the shear length and k e the poloidal wavenumber. Global transport requires w = w ma x (overlap) in EZq.…”
mentioning
confidence: 99%